Pengaruh Self-Care terhadap Kadar Glukosa Darah Puasa Pasien Diabetes Melitus Tipe-2 - Syahrizal Ramadhani; Arie Fidiawan; Tri Murti Andayani; Dwi Endarti (Faculty of Pharmacy, Universitas Gadjah Mada)
Diabetes Mellitus (DM) is a chronic hyperglycemic condition which may affect all aspects of life of the sufferer, and it can be life threatening. This problem can be minimized by doing self-care. Self-care has an influence on glycemic control, prevention of complications due to uncontrolled blood glucose and improving the quality of life for people with diabetes mellitus. This study aimed to determine the effect of self-care on fasting blood glucose of type 2 diabetics. This type of research was observational with cross-sectional design. The inclusion criteria for the study were patients with a diagnosis of diabetes mellitus aged > 18-year-old, treatment at a health center >8 weeks, had records of the last blood glucose fasting ≤1 month before the interview, while the exclusion criteria were patients who refused to participate and patients who could not communicate. Self-care measurement uses the Diabetes Self-Care Management Question (DSMQ) instrument. The number of respondents from this study was 115 people where 79,1% of respondents had a good level of self-care and 47% of respondents with fasting glucose levels that had not been achieved. The data were analyzed using Chi-square test. From this study, it was found that self-care had an effect on fasting blood glucose (OR=3,349, P<0,05). The lowest value of self-care in this study is the domain of physical activity and health-care, therefore patient motivation needs to be improved by exercise and routine check-up because self-care is one of the important factors that could control blood glucose levels.